2011
DOI: 10.1177/1073191110392497
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and Confirmatory Factor Analyses of the Asian American Racism-Related Stress Inventory

Abstract: The authors conducted exploratory and confirmatory factor analyses of the Asian American Racism-Related Stress Inventory (AARRSI) to further examine the underlying factor structure in a total sample of 1,273 Asian American participants. In the first step of analysis, an exploratory factor analysis with 651 participants yielded a 13-item two-factor solution to the data. In the second step, a confirmatory factor analysis with 622 participants supported both the 13-item two-factor model and the original 29-item t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…It is possible that discrimination from peers, which has been found to be more frequent in Asian Americans than other ethnic minorities [28, 29], may increase specific risk for SA. Another possibility is that the elevated social distress among Asian American high school students is related to discomfort in academic situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that discrimination from peers, which has been found to be more frequent in Asian Americans than other ethnic minorities [28, 29], may increase specific risk for SA. Another possibility is that the elevated social distress among Asian American high school students is related to discomfort in academic situations.…”
Section: Discussionmentioning
confidence: 99%
“…First, Asian Americans may experience SA more frequently than other ethnic groups, possibly due to factors such as socialized inhibition [20, 27] or racially motivated peer discrimination [28, 29]. While Black and Latino students report more institutional discrimination and discrimination from adults, Asian American adolescents report more harassment and discrimination from peers [30, 31].…”
mentioning
confidence: 99%
“…Because of its methodological soundness and validity this approach is commonly used in psychometric research (e.g. Miller et al, 2012;Van Prooijen and van der Kloot, 2001).…”
Section: Overviewmentioning
confidence: 99%
“…The CFA was run using the software package of IBM SPSS Amos 21. The following indices as a minimum number to be reported to support model fit were used (Kline, 2005;Crockett, 2012): (1) The model chi-square with corresponding degrees of freedom and level of statistical significance; (2) RMSEA (the Root Mean Square-Error of Approximation) with corresponding 90% confidence intervals, in the present study (RMSEA) was at or below 0.05, with values at or less than 0.05 indicate close model fit, which is customarily considered acceptable (Crockett, 2012;Worthington & Whittaker, 2006); (3) CFI (the comparative fit index) is an incremental fit index, values range between 0.0 and 1.0 with values equal to or exceeding 0.90 indicating a good fit (Crockett, 2012;Miller, Kim, Chen, & Alvarez, 2012;Hu & Bentler, 1999); and (4) Values for RMR (the root mean square residual), values range from 0.0 to 1.0 with well-fitting models obtaining values less than 0.05 (Byrne, 2006), however, values as high as 0.08 are deemed acceptable (Hu & Bentler, 1999).…”
Section: Discussionmentioning
confidence: 51%
“…To evaluate the model adequacy, four measures of fit were used: chi-square, RMR value less than or equal to 0.09, RMSEA values less than 0.10, and CFI, values greater than or equal to 0.90 are individually indicative of adequate model fit (Bentler, 1990;Browne & Cudeck, 1992;Hu & Bentler, 1999;Miller, Kim, Chen, & Alvarez, 2012;Crockett, 2012). An examination of the coefficients of hypothesized relationships between the structural and the hypothesized model suggested that the model was a reasonably acceptable fit to the data, given the guidelines described earlier.…”
Section: Confirmatory Factor Analysis Of Useppmentioning
confidence: 99%